The measurement of inclination on gravity concrete dams using the tiltmeter instrument - Radovanović Slobodan D.; Brajović Ljiljana M.; Pavić Maja L.; Đurić Srđan S.; Ranđelović Sanja D.; Milivojević Vladimir J. (Tehnika, 2015)
The measurement of inclination on gravity concrete dams using the instrument tiltmeter is described and discussed with special reference on obtained results on the dam 'Đerdap 2' acquired in the three years period. Tiltmetar way of operation is presented both through physical principle of vibrating wire sensors and through described design of the instrument. The influence of the temperature on the measurement of the slope is specially emphasized and presented through temperature correction. Processing the results of real inclination measurements on the dam 'Đerdap 2' with and without temperature correction showed the significant difference. Statistical analysis of measurement data consisted of performed regression analysis and forming of corresponding series with the expected measurement values depending on environmental conditions. At the end we give a summary conclusion on the instrument, the influence of temperature on the measurement and statistical model.